The death of Ivan Ilych: A blueprint for intervention at the end of life - Papadimos, Thomas J (Medknow Publications & Media Pvt Ltd, 2011)
Medical practice and the field of humanities frequently intersect. It is uncanny how problems presented or described in literature that are several hundred years old still present themselves to us on a regular basis. Often, our answers to these dilemmas are not perfect, but we continue our attempts at providing solutions through an enlightened evolution of our thought and approaches. Leo Tolstoy's novella, The Death of Ivan Ilych, is a classic piece of literature that allows a view of the dying process in an ordinary human being, and presents us with an opportunity to observe, not only the intersection of medicine and humanities, but also that of critical care and palliative medicine. Here Tolstoy, through his keen observation of the human condition at the end of life, allows us an opportunity to view a 19(th) century perspective that has an all too familiar persistence that needs a 21(st) century intervention.